Upaya Meningkatkan Penyesuaian Diri Siswa “F” terhadap Perubahan Kondisi Keluarga melalui Konseling Realitas di Sekolah Menengah Atas Negeri 1 Indralaya Utara - Sary, Devita; Harlina; Hakim, Imron A (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2014)
The objective of this study was to improve self adaptation of student “F” toward the changes in family condition through reality counseling in SMA N 1 Indralaya Utara. Guidance and counseling action research method was used in this study. The data wereanalyzed in a descriptive qualitative way. Observation and interview were done for collecting the data. The result showed that counseling reality which emphasizes on the desire exploration and action planning by the counselee could improve the self adaptation of student “F” toward the changes of family condition. This result was supported by the score improvement of the interview before and after the treatment in the second cycle. In the first cycle, the reality counseling focused on the expressing desire exploration of the counselee toward the family. In the second cycle, the counseling reality process emphasized on the step of action planning especially giving the positive encouragement and motivating the counselee to do the action which has been well planned. Thus, the counseling reality could be used to improve the self adaptation of student “F” toward the changes of family condition.